Metaphysics of a city: the archetypal phaenomenon of the desert fathers, or the lessons of the perfect silence - Sodeika, Tomas (Religija ir kultūra, 2008)
The modern man, used to a discursive reading and explanation in mystical literature may find the Sayings of Desert Fathers difficult to assimilate and to apply to everyday life. The first thing that strikes a reader is the insistence in the stress laid on the necessity of askesis. Such a problem was unknown to the Desert Fathers. The experience which God in His infinite love gives to those who seek Him with their whole heart is always a gift and cannot therefore be deserved. The essence of the spirituality of the desert is that there is no doctrine that would be learned. Desert Fathers had the hard work of striving to re-direct every part of body and soul to God, and that is what they meant by prayer. Prayer was not only an activity undertaken for a few times each day, but rather a life continually turned towards God in silence.
Keywords: Desert Fathers; prayer; silence